Impact property of TiAl3–Ti laminated composite fabricated from metallic sandwich - Chatdanai Boonruang (2020)
© 2019 The Authors TiAl3–Ti Laminated composite has been fabricated by hot pressing of titanium–aluminium sandwich in order to improve impact toughness of TiAl3. Fabrication process has been reported and structure evolution, phase portion, hardness, impact toughness, and fractography of the composite are investigated using XRD, XPS, SEM, EDS, hardness test, and impact test. The results show formation of TiAl3 and production of TiAl3–Ti laminated composite after the sandwiches have been hot pressed at 600 and 650 °C for 24 h in low vacuum system. TiAl3–Ti thickness ratio attributed to phase portion and hardness of TiAl3–Ti interface region are shown to be promoted by fabrication temperature. Fractography and EDS results can allow the impact–fracture mechanism of composite to be proposed. The impact toughness of composite can be improved by using low fabrication temperature in order to reduce TiAl3–Ti thickness ratio.